Efficacy of spironolactone in adult acne in polycystic ovary syndrome patients an original research - Neha Rani; Prashant Kumar; Anup Kumar Mishra; Bala Yadu Vamsi Sankuratri; Sanjana Sethi; Kalyani Gelada; Heena Tiwari (Wolters Kluwer Medknow Publications, 2021)
Introduction: This prospective clinical trial was designed to assess the effects of a long-term therapy with spironolactone, with and without dietary-induced weight-loss, on clinical features, lipid profile, and insulin levels in women with polycystic ovary syndrome (PCOS). Materials and Methods: Twenty-five patients (range of age 16-32 year; 13 lean and 12 overweight) fulfilling formal diagnostic criteria for PCOS (oligomenorrhea and/or amenorrhea, biochemical and/or clinical evidence of hyperadrogenism) were studied at baseline and then received oral spironolactone (100 mg/die) for 12 months; association with lifestyle modifications was recommended to all overweight patients. Clinical, endocrine, and metabolic parameters (oral glucose tolerance test [OGTT], lipid profile) were measured at baseline and at the end of the antiandrogen treatment. Results: The therapy was associated with a significant average decline of triglycerides in overweight subjects and with increased high-density lipoprotein-cholesterol levels in lean patients. The insulin levels at 60 min during OGTT, homeostasis model assessment-insulin resistance and area under curve of insulin were significantly lowered in overweight women after 12 months of spironolactone and weight loss and no negative changes in insulin secretion and sensitivity were observed in PCOS women after pharmacological treatment alone. Conclusion: The efficacy of spironolactone on the androgenic clinical aspects of PCOS has been confirmed in this study. Furthermore, our data show that long-term treatment with spironolactone exerts no negative effects on lipoprotein profile and glucose metabolism; more relevant beneficial effects on glucose and lipid metabolism were observed when the antiandrogen was associated with weight loss in overweight PCOS women.